The Role of China’s “Five Principles of Peaceful Coexistence” in Establishing a Multipolar World Order - A. A. Nechai (Евразийская интеграция: экономика, право, политика, 2023)
In the 21st century, with the emergence on the world stage of a new strong actor in international relations — the People’s Republic of China — it became obvious that the Western model of global governance must be revised or at least an alternative must be proposed to it. China has consistently advocated the formati on of a multipolar world order built on the principles of pluralism of interests and civilizational diversity, which are reflected in the concept of the Five Principles of Peaceful Coexistence. The idea of peaceful coexistence is more relevant than ever.Aim. The purpose of this study is to determine the use of the Five Principles of Peaceful Coexistence in China’s foreign policy strategy.Tasks. Analyze the content of the “Five Principles of Peaceful Coexistence” and trace their reflection in the PRC’s foreign policy activities by the example of the state’s actions in relation to conducting a Special military operation.Methods. During the study, the author used the method of historical retrospective, as we ll as the method of analyzing documents.Results. The relevance of the application of the concept of “Five Principles of Peaceful Coexistence” in the foreign policy of China was substantiated; each principle was characterized, the peculiarities of their application in relation to the conduct of Special military operation were revealed.Conclusions. The origins of the Five Principles of Peaceful Coexistence can be seen in Confucianism, which implies harmony without unification. In the 21st century, China is actively taking initiatives to form a new world order, taking the “Five Principles of Peaceful Coexistence” as a basis, working to create a positive image of the country. The principles of peaceful coexistence are reflected in the state’s position on the special military operation in Ukraine: China calls to respect national sovereignty, observing the principles of the UN Charter, supports a peaceful dialogue between the two countries, which will take into account the interests of both sides, and follows the principle of non-interference in the internal affairs of Russia, abstaining from voting in the UN Security Council on the Ukrainian issue, condemns sanctions as an unacceptable instrument of influence in world politics. PRC officials are convinced that the conflict was provoked by NATO’s eastward expansion and that it is part of Russia’s defense policy, as NATO expansion poses a direct threat to Russian national security. Defending peace and opposing armed clashes is a historical and cultural tradition China has maintained during the conflict.